Tarsocrural Instability in Cats: Combined Internal Repair and Transarticular External Skeletal Fixation - Hammer, Meike; Irubetagoyena, Iban; Grand, Jean-Guillaume (VCOT Open, 2020)
Objective The aim of this study was to report outcomes after combined internal repair and transarticular external skeletal fixation (TESF) for the treatment of tarsocrural joint instabilities (TCI) in cats.Materials and Methods Open reduction of the tarsal joint was performed followed by combined (1) internal repair (tibial/ fibular malleolar osteosynthesis or primary ligament suture and/or prosthetic ligament repair) and (2) temporary TESF. Stability of the tarsus was determined at short-term follow-up (4–8 weeks postoperatively). Short-term complications were evaluated and midterm outcome assessed by an owner telephone questionnaire.Results Fourteen cats were included of which nine had open TCI. Median time for frame removal was 47 days. Eleven patients had satisfactory stability of the tarsus at short-term follow-up. Catastrophic complications occurred in three cats consisting of extensive skin necrosis of the paw with subsequent hindlimb amputation in two and multiple digit amputations in one cat. Major complications occurred in one cat with persistent TCI requiring pantarsal arthrodesis. Nine cat owners indicated a ‘full or acceptable’ outcome at midterm (median, 1.5 years).Conclusion Close monitoring in the postoperative period until TESF removal is important for early identification of complications. Despite good joint stability at short-term, persistent or recurrent lameness at midterm can occur.
Keywords: tarsocrural joint instability; internal fixation; transarticular external skeletal fixation; cats